2016
DOI: 10.7575/aiac.ijkss.v.4n.4p.18
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Short-Term Jump Squat Training With and Without Chains on Strength and Power in Recreational Lifters

Abstract: Background: The use of chains in resistance training is a way to accommodate the muscular strength curve. Short-term training and jump squats have been shown to increase back squat strength, but not in conjunction with each other or with chains. Jump squats have also been used to increase jump height and power. Objectives: The purpose of this study was to investigate the effects of short-term jump squat training with and without chains on strength and power. Methods: Thirty-one resistance-trained men volunteer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 32 publications
(52 reference statements)
0
8
0
1
Order By: Relevance
“…Jump height (JH) is an important component in sports, such as basketball and volleyball, which require explosive lower body power (Archer et al, 2016). A common test to determine power is the vertical jump.…”
Section: Introductionmentioning
confidence: 99%
“…Jump height (JH) is an important component in sports, such as basketball and volleyball, which require explosive lower body power (Archer et al, 2016). A common test to determine power is the vertical jump.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 22 reports that comprised both trained and untrained participants were included for the meta-analysis [ 8 , 16 , 22 , 23 , 24 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. As shown in Figure 2 , VRT and CRT significantly differed in the improvement of the maximum strength of the subjects (ES = 0.80; 95% CI: 0.42–1.19).…”
Section: Resultsmentioning
confidence: 99%
“…The results of several of studies have not found that VRT is better than CRT for the development of maximum strength [ 16 , 22 , 23 ]. In a study by Cronin et al [ 24 ], participants performed supine jump squat training with a load of 8–15 repetition maximum (RM) with or without elastic bungees. The results revealed that maximum strength of participants with elastic bungees was not better than that of participants without bungees (non-bungee squat) [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations